Copra meal dietary fiber and its effect on the serum cholesterol levels of experimental rats - Hilario,Dahlia R. (1990)
ABSTRACT Twenty male albino Sprague-Dawley rats from the CVM colony were used in the experiments. They were randomly distributed into two groups, with one group fed with the unsubstituted diet and became the control group and the other group fed with coprameal-substituted diet. Copra meal at 30% substitution resulted to a significant decrease in the daily weight gain of the rats of which the control group has a mean of 0.02 ± 0.54 g and the treated ones, 2.44 ± 0.30 g. The transit time was also significantly shortened in the treated group with a mean of 7.30 ± 0.49 hrs while the control's residence time was 9.65 ± 0.68 hrs. As for their moisture content, the control group had a mean of 58.12 ± 9.66% while the treated rats had a mean of 70.72 ± 5.11%. Furthermore, the mean fecal density of 0.7314 ± 0.0925 g/mL for the control rats was significantly lower than that of the treated rats' means of 0.09438 ± 0.844 g/mL. Lastly, in the serum cholesterol analysis, the treated group's serum cholesterol level of 59.00 ± 9.29 mg/ 100 mL was significantly decreased relative to the control which had a group mean of 85.40 ± 4.93 mg/100mL. It was confirmed in this study that copra meal has the ability to increase water-holding capacity, increase fecal bulk, shorten transit time, lower caloric intake and finally, lower serum cholesterol levels. Thus it can be included here that copra meal is an excellent source of dietary fiber.